The Paleobiolinguistics of the Common Bean (Phaseolus vulgaris L.) - Cecil H. Brown; Charles R. Clement; Patience Epps; Eike Luedeling; Søren Wichmann (Ethnobiology Letters, 2014)
Paleobiolinguistics is used to determine when and where the common bean (Phaseolus vulgaris L.) developed significance for prehistoric groups of Native America. Dates and locations of proto-languages for which common bean terms reconstruct generally accord with crop-origin and dispersal information from plant genetics and archaeobotany. Paleobiolinguistic and other lines of evidence indicate that human interest in the common bean became significant primarily with the widespread development of a village‐farming way of life in the New World rather than earlier when squash and maize and a few other crops became important.